Hawksmaid : the untold story of Robin Hood and Maid Marian - Lasky, Kathryn (Harper, 2010)
In twelfth-century England, Matty grows up to be a master falconer, able to communicate with the devoted birds who later help her and Fynn, also known as Robin Hood, to foil Prince John's plot to steal the crown.